Pelatihan Penulisan Karya Ilmiah Untuk Keberhasilan Publikasi Mahasiswa PKK - Wikan Budi Utami; Sri Adi Widodo; Fikri Aulia (Jurnal Pengabdian Sains dan Humaniora, 2024)
The problems faced by PKK students are difficulties in determining a topic or problem, determining a title, making an introduction, and determining references. The aim of this activity is to increase students' knowledge and abilities in compiling scientific papers, socialize the importance of writing scientific papers, and to improve students' abilities in determining titles and making introductions that comply with the guidelines for writing scientific papers. The methods used in this service are lecture methods, discussion methods, training activities and evaluation. This activity succeeded in improving the ability to compose scientific papers. Motivation, enthusiasm and passion were visible from the students while taking part in the activities, this could be seen from the number of students who took part in the discussions and all the students submitted scientific writing products.